Avaliação do nível de estresse de alunos de medicina e associações entre estilos de aprendizagem e metodologias de ensino - Bergamo, Ingrid (2018)
Stress can cause physical and mental health problems, reduce students' self-esteem, and affect their academic performance. It is a psychological shift that is becoming more frequent among medical students than the general population, and these levels of stress can affect academic performance. We will compare the students' level of stress with methodology used in each of the medical schools, along with their learning style. When the individual learning style does not fit the method used by the student's university, the shock can become another stressor. We evaluated learning styles and stress levels among medical students of a medical school and another university in the state of São Paulo applying different teaching methods. The results showed that most of the students presented reflective learning style in both schools (60.4% in UNOESTE and 32.7% in FACERES) and high levels of overall stress among students (68.2% in UNOESTE and 74.0% in FACERES). In the resistance phase (81.5%), there was a predominance of psychological symptoms of stress on physical symptoms in both faculties (75.9% of students in UNOESTE and 86.5% in FACERES). Female students were found to have higher stress levels than their male counterparts (72.0% and 55.0%, respectively). This is the first study to compare stress levels, learning styles and teaching methodologies at two different medical schools.